Molecular studies of Tobacco Rattle Virus (TRV) infection in potato - Sahi, Ghulam Mustafa (The University of Edinburgh, 2016)
Tobacco rattle virus (TRV) is a bipartite plant virus that infects potato tubers to produce the spraing or corky ring spot (CRS) disease of potato. TRV is primarily a soil-borne pathogen that is vectored by trichodorid nematodes. Spraing is characterized by the production of brown arcs and flecks in the tuber flesh or circular rings on its external surface. Spraing has been described as a hypersensitive response (HR). However, the genetic and biochemical nature of spraing had not been previously investigated experimentally. I have conducted studies to reveal the gene expression and the biochemical basis for spraing formation. Microarray analysis of RNA extracted from tuber-tissue showing spraing symptoms, revealed up-regulation of several defence related genes. Quantitative RT-PCR (qRT-PCR) of some of the differentially-expressed potato defence related genes was done for verification of the microarray data. Biochemical tests for cell death response reactions and staining for HR-related compounds or production of reactive oxygen species (ROS) also revealed the operation of HR-related processes in the spraing-affected tuber. Uneven distribution of the TRV RNA-1 in a spraing-symptomatic tuber also supports the notion that it’s a virus-induced HR-response. RNA-2 of TRV besides coding for the CP also carries the non-structural genes, 2b and 2c genes that are responsible for the nematode transmission of TRV. Fifteen different TRV recombinant isolates were prepared and the influence of the RNA-2 specific genes, encoded by a range of TRV-isolates, in causing infection among different cultivars of potato was also evaluated. Investigations were conducted to identify TRV-susceptible genotypes in which virus could move systemically and accumulate to a sufficient level to be useful for TRV-infection and VIGS-related studies for functional analysis of potato genes.
Keywords: gene expression; tobacco rattle virus; TRV